Symmetry-driven spontaneous self-assembly of nanoscale ceria building blocks to fractal superoctahedra - Kuchibhatla, Satyanarayana V. N. T.; Karakoti, A. S.; Sayle, Dean C.; Heinrich, H.; Seal, S. (American Chemical Society (ACS), 2009)
A combination of long-term aging studies and molecular dynamics (MD) simulations has been successfully used to explain the time-dependent hierarchical assembly of ceria nanoparticles (CNPs). When the CNPs were aged in as-synthesized condition at room temperature in water, it was observed that the individual 3−5 nm CNPs result in octahedral superstructures through a fractal assembly. This hierarchical fractal self-assembly was observed despite the absence of any surfactant, at room temperature, and under atmospheric pressure. High resolution transmission electron microscopy (HRTEM) and fast Fourier transform (FFT) analysis have been used to explore the assembly of the individual nanoparticles into fractal superoctahedra. Both experimental work and theoretical analysis showed that the initial octahedral and truncated octahedral seeds symmetrically assemble and result in the superoctahedra with intermediate transformation step